Jan A. Ali, Islam and Muslims in Australia: Settlement, Integration, Shariah, Education and Terrorism - Ansari, Mahsheed (Journal for the Academic Study of Religion, 2022)
Jan A. Ali, Islam and Muslims in Australia: Settlement, Integration, Shariah, Education and Terrorism, Melbourne: Melbourne University Publishing, 2020, pp. 256, ISBN: 9780522877076 (hbk). $69.99.